2017
DOI: 10.1016/j.devcel.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Zygotic Transition Is Initiated in Unicellular Plant Zygotes with Asymmetric Activation of Parental Genomes

Abstract: The zygotic transition, from a fertilized egg to an embryo, is central to animal and plant reproduction. Animal embryos depend upon maternally provided factors until zygotic genome activation (ZGA). In plants, the timing and parental genome contributions to ZGA are unresolved. Here, we use the flowering plant Oryza sativa (rice) to characterize transcriptomes of time-staged isogenic and hybrid zygotes following fertilization. Large-scale transcriptomic changes were observed in unicellular zygotes, including up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
118
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 46 publications
13
118
0
1
Order By: Relevance
“…Three lines of evidence indicated RNA contamination from ovary in egg cells was minimal. First, our egg or zygote isolation method has previously been shown to have little mRNA contamination from maternal tissue (Anderson et al 2017;Li et al 2019). Second, we performed differential expression analysis of the miRNAs, and found that eight miRNAs had high levels in all three replicates of ovary but were nearly undetectable in all six replicates of egg cells (Fig.…”
Section: Distinct Mirna Expression Patterns In Gametesmentioning
confidence: 95%
See 3 more Smart Citations
“…Three lines of evidence indicated RNA contamination from ovary in egg cells was minimal. First, our egg or zygote isolation method has previously been shown to have little mRNA contamination from maternal tissue (Anderson et al 2017;Li et al 2019). Second, we performed differential expression analysis of the miRNAs, and found that eight miRNAs had high levels in all three replicates of ovary but were nearly undetectable in all six replicates of egg cells (Fig.…”
Section: Distinct Mirna Expression Patterns In Gametesmentioning
confidence: 95%
“…Analysis of published gamete transcriptomes did not reveal any obvious explanation for egg or sperm siRNA patterns, though they did show dramatic differences in mRNA levels for some RdDM factors such as RDR2 (Anderson et al 2013;Anderson et al 2017) (Supplemental Fig. 7).…”
Section: Distinct Genome-wide Patterns Of 24nt Sirnas In Gametesmentioning
confidence: 98%
See 2 more Smart Citations
“…It was further suggested that this is epigenetically regulated (e.g., Baroux and Grossniklaus 2015; Grimanelli et al 2005; Nodine and Bartel 2012; Zhao et al 2017; Zhao and Sun 2015). However, recent evidence using genome-wide transcriptional analysis in maize and rice revealed that zygotic genome activation occurs soon after fertilization, exhibiting a highly dynamic and partially transient pattern of gene expression (Chen et al 2017; Anderson et al 2017). These include genes involved in hormone biosynthesis and responses, RdDM, and other pathways associated with massive chromatin changes after fertilization.…”
Section: Do Abiotic Stresses Influence Fertilization Mechanisms?mentioning
confidence: 99%